On Patient Experience and Anxiety During Treatment With Magnetic Resonance–Guided Radiation Therapy - Jasmijn M. Westerhoff, MD; Pim T.S. Borman, PhD; Reijer H.A. Rutgers, BSc; Bas W. Raaymakers, PhD; Neil Winchester, MSc; Helena M. Verkooijen, PhD; Martin F. Fast, PhD (Advances in Radiation Oncology, 2024)
Purpose: To assess patient experience and anxiety during magnetic resonance (MR)–guided radiation therapy (MRgRT) using a hybrid 1.5Tesla (T) MR-guided linear accelerator (MR-Linac) when offered calming video content. Methods and Materials: A single-center study was conducted within the Multi-Outcome Evaluation of Radiation Therapy Using the MR-Linac (MOMENTUM) cohort. Patients were offered to watch calming video content on a video monitor during treatment. Questionnaires were used to assess patient experience (MR-Linac patient-reported experience) and anxiety (State-Trait Anxiety Inventory, STAI) at first treatment fraction (M1) and at third, fourth, or fifth treatment fraction (M2). Paired t tests were used to test for significant differences, and effect sizes (ESs) were used to estimate the magnitude of the difference. Results: Between November 2021 and November 2022, 66 patients were included. The majority were men (n = 59, 89%). MRgRT was most frequently delivered to prostate cancer (n = 45, 68%) followed by a lesion in the pancreas (n = 8, 12%). At M1 and M2, 24 of 59 patients (41%) preferred to watch calming video content. One patient was not able to look at the video monitor comfortably at M1. Patient experience was generally favorable or neutral; tingling sensations were reported by 17% of patients. Anxiety levels were high (16%), moderate (18%), or low to none (67%) prior to M1. STAI scores were 33 (SD, 9) prior to M1 and 29 (SD, 7) after M1 (ES, 0.7; P < .001). STAI scores were 32 (SD, 9) prior to M2 and 31 (SD, 8) after M2 (ES, 0.4; P = .009). Conclusions: Patients were able to comfortably view the video monitor during MRgRT. Consequently, this setup could be used for future applications, such as biofeedback. A sizable minority of patients preferred to watch calming videos that distracted them during treatment. Although the patients’ experience was overall excellent, anxiety was reported. Anxiety levels were highest prior to treatment and decreased after treatment.